2015
DOI: 10.4238/2015.march.30.3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of signal transducer and activator of transcription 3 (STAT3) suppresses ovarian cancer growth, migration and invasion and enhances the effect of cisplatin in vitro

Abstract: ABSTRACT. The aim of the present study was to investigate the antiovarian cancer effect of the inhibitor of signal transducer and activator of transcription 3 (STAT3), WP1066. Western blot was used to detect the phosphorylation of STAT3 in ovarian cancer cell line SKOV3 and cisplatin-resistant ovarian cancer cell line SKOV3/DDP. MTT and colony-forming assays were performed to evaluate the viability and growth of ovarian cancer cells. The apoptosis of ovarian cancer cells was determined by flow cytometry. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Its inhibition has been shown to have antitumor activity, and to reverse the sensitivity to therapy in different cancer types [2830], including ovarian cancer [31, 32]. Recently, a STAT3 role in DDP resistance and acquisition of stem-like features by STAT3 activation has also been described [33].…”
Section: Discussionmentioning
confidence: 99%
“…Its inhibition has been shown to have antitumor activity, and to reverse the sensitivity to therapy in different cancer types [2830], including ovarian cancer [31, 32]. Recently, a STAT3 role in DDP resistance and acquisition of stem-like features by STAT3 activation has also been described [33].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ALD518, a humanized anti-IL-6 antibody, helps NSCLC patients obtain therapeutic benefits against cachexia, anemia, and drug resistance 89 . WP1066, a JAK2 inhibitor, suppresses ovarian cancer growth, migration, and invasion; this inhibitor also enhances the chemosensitivity of ovarian cancer cells and decreases the rate of STAT3 phosphorylation 90 . Direct inhibitors directly block the SH2, DNA-binding, and N-terminal domains of STAT3 to suppress protein dimerization, to inhibit DNA binding, and to prevent nuclear translocation, respectively.…”
Section: Pivotal Biological Functions Of Stat3 In Cancermentioning
confidence: 99%
“…Chemoresistance has previously been found to associate with the failure of cisplatin to induce apoptosis 22 . Numerous studies have demonstrated great contribution of NF-κB and STAT3 to cisplatin resistance via suppression of cisplatin-induced apoptosis 28 - 31 . The activation level of NF-κB is higher in cisplatin-resistant human epidermoid carcinoma cells and curcumin, an inhibitor of NF-κB activation, sensitizes the cisplatin-resistant cells by down-regulation of apoptosis-related proteins such as Bcl-2 28 .…”
Section: Discussionmentioning
confidence: 99%